Antibiotic resistance in microbes: History, mechanisms, therapeutic strategies and future prospects. Issue 12 (December 2021) - Uddin, Tanvir Mahtab; Chakraborty, Arka Jyoti; Khusro, Ameer; Zidan, BM Redwan Matin; Mitra, Saikat; Emran, Talha Bin; Dhama, Kuldeep; Ripon, Md. Kamal Hossain; Gajdács, Márió; Sahibzada, Muhammad Umar Khayam; Hossain, Md. Jamal; Koirala, Niranjan
Abstract: Antibiotics have been used to cure bacterial infections for more than 70 years, and these low-molecular-weight bioactive agents have also been used for a variety of other medicinal applications. In the battle against microbes, antibiotics have certainly been a blessing to human civilization by saving millions of lives. Globally, infections caused by multidrug-resistant (MDR) bacteria are on the rise. Antibiotics are being used to combat diversified bacterial infections. Synthetic biology techniques, in combination with molecular, functional genomic, and metagenomic studies of bacteria, plants, and even marine invertebrates are aimed at unlocking the world's natural products faster than previous methods of antibiotic discovery. There are currently only few viable remedies, potential preventive techniques, and a limited number of antibiotics, thereby necessitating the discovery of innovative medicinal approaches and antimicrobial therapies. MDR is also facilitated by biofilms, which makes infection control more complex. In this review, we have spotlighted comprehensively various aspects of antibiotics viz. overview of antibiotics era, mode of actions of antibiotics, development and mechanisms of antibiotic resistance in bacteria, and future strategies to fight the emerging antimicrobial resistant threat.